2014
DOI: 10.1089/apc.2013.0354
|View full text |Cite
|
Sign up to set email alerts
|

HIV+ Men Need Reproductive Counseling Too: Assessing Childbearing Goals and Provider Communication Among HIV+ Male Patients in Rio de Janeiro, Brazil

Abstract: We assessed reported communication with HIV providers about reproductive plans among HIV+ men in Rio de Janeiro, Brazil, and factors associated with having had such communication. A total of N=311 HIV+ men (18-50 years) receiving HIV care at one of six public primary care clinics in Rio de Janeiro between 2008-2009 were surveyed. We used descriptive statistics, and multivariate logistic regression to identify factors associated with communication about childbearing with an HIV provider. HIV+ male patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…According to the search strategy we retrieved 5,314 articles, of which 1,795 were duplicates. Finally, 50 articles were assessed for eligibility in these meta-analyses after full-text screening [ 10 , 14 , 27 74 ]. A flowchart of the literature search was presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the search strategy we retrieved 5,314 articles, of which 1,795 were duplicates. Finally, 50 articles were assessed for eligibility in these meta-analyses after full-text screening [ 10 , 14 , 27 74 ]. A flowchart of the literature search was presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most often it was female patients who initiated these conversations, despite the fact that both partners should be involved in decision making and planning. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 31% of HIV-infected men and women in care in Uganda reported wanting to have children, yet nearly two-thirds had never discussed their fertility desires with a provider [ 5 ]. Globally, client conversations with HIV care providers about pregnancy plans are infrequent, as shown in studies from sub-Saharan Africa [ 16 20 ], South America [ 21 23 ], North America [ 24 26 ], and Europe [ 27 ].…”
Section: Introductionmentioning
confidence: 99%